The Tiger Sulfide Chimney, Yonaguni Knoll IV Hydrothermal Field, Southern Okinawa Trough, Japan: The First Reported Occurrence of Pt–Cu–Fe‐Bearing Bismuthinite and Sn‐Bearing Chalcopyrite in an Active Seafloor Hydrothermal System. Issue 4 (24th September 2013) - Gena, Kaul; Chiba, Hitoshi; Kase, Katsuo; Nakashima, Kazuo; Ishiyama, Daizo
Abstract A sulfide chimney ore sampled from the flank of the active Tiger vent area in the Yonaguni Knoll IV hydrothermal field, south Okinawa trough, consists of anhydrite, pyrite, sphalerite, galena, chalcopyrite and bismuthinite. Electron microprobe analysis indicates that the chalcopyrite contains up to 2.4 wt% Sn, whereas bismuthinite contains up to 1.7 wt% Pt, 0.8 wt% Cu and 0.5 wt% Fe. The Sn‐rich chalcopyrite and Pt–Cu–Fe‐bearing bismuthinite are the first reported occurrence of such minerals in an active submarine hydrothermal system. The results confirm that Sn enters the chalcopyrite as a solid solution towards stannite by the coupled substitution of Sn4+Fe2+ for Fe3+Fe3+, whereas Pt, Cu and Fe enter the bismuthinite structure as a solid solution during rapid nucleation. The fluid inclusions homogenization temperatures in anhydrite (220–310°C) and measured end‐member temperature of the vent fluids on‐site (325°C) indicate that Sn‐bearing chalcopyrite and Pt–Cu–Fe‐bearing bismuthinite express the original composition of the minerals that precipitated as metastable phases at a temperature above 300°C. The result observed in this study implies that sulfides in ancient volcanogenic massive sulfide deposits have similar trace element distribution during nucleation but it is remobilised during diagenesis, metamorphism or supergene enrichment processes.